POPULASI KALIANDRA (Calliandra sp.) DI STASIUN RISET BLOK PASIR BATANG TAMAN NASIONAL GUNUNG CIREMAI - Aditya, Aditya; Supartono, Toto; Nurdin, Nurdin (Faculty of Forestry and Environment, Universitas Kuningan, 2023)
Invasive species are reported to have encroached on conservation areas including the Mount Ciremai National Park area. One of the invasive species identified in Mount Ciremai National Park is the Kaliandra plant (Calliandra sp.). The distribution of calliandra (Calliandra sp.) mainly occurs because the arable land within the area has actually become open land, not in accordance with the previous Community Forest Planting concept. This study aims to determine the density of calliandra and determine the pattern of distribution of populations of calliandra found. The research was carried out in the Pasir Batang Block Research Station Forest area of Mount Ciremai National Park covering an area of ± 90 Ha from March to June 2022. The data collection method used was the Gentry method and the analytical method used was vegetation density, frequency distribution, and population distribution patterns. The population of Calliandra at the Pasir Batang Block Research Station, Mount Ciremai National Park, found 2 types of Calliandra, namely White Calliandra (Calliandra tetragona) and Red Calliandra (Calliandra calothyrsus). The results showed that the vegetation density of white calliandra was 5,364 ind/ha and red calliandra 1,614 ind/ha. Then the scatter pattern obtained from white calliandra is grouped with a standardized Morisita Index value of 0.5070 and also for red calliandra is grouped with a standardized Morisita Index value of 0.5307.Spesies invasif dilaporkan telah merambah kawasan konservasi termasuk kawasan Taman Nasional Gunung Ciremai. Salah satu spesies invasif yang teridentifikasi di Taman Nasional Gunung Ciremai adalah tumbuhan Kaliandra (Calliandra sp.). Sebaran kaliandra (Calliandra sp.) terutama terjadi karena lahan garapan di kawasan tersebut justru menjadi lahan terbuka, tidak sesuai dengan konsep Penanaman Hutan Kemasyarakatan sebelumnya. Penelitian ini bertujuan untuk mengetahui kepadatan kaliandra dan mengetahui pola sebaran populasi kaliandra yang ditemukan. Penelitian dilaksanakan di Hutan Stasiun Penelitian Blok Pasir Batang Taman Nasional Gunung Ciremai seluas ± 90 Ha pada bulan Maret sampai dengan Juni 2022. Metode pengumpulan data yang digunakan adalah metode Gentry dan metode analisis yang digunakan adalah kerapatan vegetasi, distribusi frekuensi, dan pola distribusi populasi. Populasi Kaliandra di Stasiun Penelitian Blok Pasir Batang Taman Nasional Gunung Ciremai ditemukan 2 jenis Kaliandra yaitu Kaliandra Putih (Calliandra tetragona) dan Kaliandra Merah (Calliandra calothyrsus). Hasil penelitian menunjukkan kepadatan vegetasi kaliandra putih sebesar 5.364 ind/ha dan kaliandra merah 1.614 ind/ha. Kemudian pola sebaran yang didapat dari kaliandra putih dikelompokkan dengan nilai Indeks Morisita terstandar sebesar 0,5070 dan juga untuk kaliandra merah dikelompokkan dengan nilai Indeks Morisita terstandar sebesar 0,5307.